2018
DOI: 10.1891/1061-3749.26.3.470
|View full text |Cite
|
Sign up to set email alerts
|

Using Cluster Analysis to Identify Subgroups of College Students at Increased Risk for Cardiovascular Disease

Abstract: Background and Purpose: To examine the co-occurrence of cardiovascular risk factors and cluster subgroups of college students for cardiovascular risks. Methods: A cross sectional descriptive study was conducted using co-occurrence patterns and hierarchical clustering analysis in 158 college students. Results: The top co-occurring cardiovascular risk factors were overweight/obese and hypertension (10.8%, n = 17). Of the total 34 risk factors that co-occurred, 30 of them involved being overweight/obese. A six-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Several studies have reported prevalence of clusters of CVD risk factors in the general population. [19][20][21] Few studies have identified cluster types based on sleep pattern 22 , behavioural characteristics 23 , and cardiometabolic health 24 in CMVDs, yet little is known about clusters of CVDs risk factors among CMVDs; though the prevalence of these risk factors have been well described in this group. 25,26 Evidence-based practices have shown that chronic diseases such as hypertension, diabetes, and hyperlipidemia are better treated together since they often occur in clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported prevalence of clusters of CVD risk factors in the general population. [19][20][21] Few studies have identified cluster types based on sleep pattern 22 , behavioural characteristics 23 , and cardiometabolic health 24 in CMVDs, yet little is known about clusters of CVDs risk factors among CMVDs; though the prevalence of these risk factors have been well described in this group. 25,26 Evidence-based practices have shown that chronic diseases such as hypertension, diabetes, and hyperlipidemia are better treated together since they often occur in clusters.…”
Section: Introductionmentioning
confidence: 99%